“Postmodern ecofeminist theories and politics“ - Mušić, Lejla (IJRDO - Journal of Social Science and Humanities Research, 2016)
Postmodern ecofeminist theories as the key theories for transnational and global cooperations and peace agreemants offer the global approaches towards the democracy, as they involve analyzes of intersection of ontemporary ecological problems, social system, and gender problem. The juxtaposed nationalism results in ethnocentrism, sexual racism, ethnical racism (Vlaisavljević 2009, 179-209). Environmental nationalism as a project, rejects all three forms of discrimination proposing the idea of supranational and transnational unions based on need for ecological problems solution. Therefore the borders of nation-states, should be moved towards the wider areas of bioregional cooperation, and communal care for climate changes. Ecofeminist Eislar Rian in her work Ecofeminist manifesto (1987) holds that the social system of Minoan period of rule on Greek island Crete, was the only true democracy. Deconstruction of gender dichotomies results in transgender society. Contemporary sociological perspective includes transnational identities. . „Environmentalist nationalism represents superior form of nationalism, because of its luck for tendentiousness towards the racism, ethnical violence and militarism, it is rather based on bioregionalism“ ( Galić 2000, 34).